Predictors of Early Retention in Peer Recovery Program for Justice-Involved Individuals With Opioid Use Disorder - Rebecca Sutter-Barrett; Nancy R. B. Spencer; Nora Elnahas; Steven Austin; Allen West; Allison West; Caitlyn Mundie (Journal of Correctional Health Care, 2026)
Retention in peer recovery programs is critical for individuals with opioid use disorder involved in the criminal justice system. This study examined predictors of one-month retention in the Empowered Communities Opioid Project, a peer recovery support program serving adults across five Virginia health districts. Baseline survey data from 255 participants enrolled between September 2022 and February 2025 were analyzed. Measures included demographic, social, economic, mental health, health care access, and substance use factors. Logistic regression models identified predictors of retention. Of the 255 participants, 127 (49.8%) were retained at one month. Program site was the strongest predictor of retention, with participants at Site 2 significantly less likely to be retained than those at Site 1 (odds ratio = 0.45, p = .004). Recent opioid use and prior overdose were also associated with lower retention.